Ammodytes hexapterus Pallas 1814 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Ammodytes hexapterus Pallas, 1814. Arctic Sand Lance. To at least 28 cm (11 in) TL (Mecklenburg et al. 2016). East Siberian, Chukchi, and Beaufort Seas eastward to Hudson and Ungava Bays (Mecklenburg et al. 2018, Falardeau et al. 2017), southward through eastern Bering Sea to Unimak Pass, and western Bering Sea to southeastern Kamchatka and Sea of Okhotsk (Mecklenburg et al. (2016). Pelagic and benthic; marine and brackish waters (Dyldin and Orlov 2017); depth: intertidal to 275 m (902 ft) (Mecklenburg et al. 2018). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 193, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...